IL-17A causes depression-like symptoms via NFκB and p38MAPK signaling pathways in mice: Implications for psoriasis associated depression. (September 2017) - Nadeem, Ahmed; Ahmad, Sheikh F.; Al-Harbi, Naif O.; Fardan, Ali S.; El-Sherbeeny, Ahmed M.; Ibrahim, Khalid E.; Attia, Sabry M.
Highlights: Psoriatic inflammation is associated with depression-like symptoms in mice. Psoriatic inflammation elevates systemic IL-17A expression in innate/adaptive immune cells. IL-17A administration per se leads to depression-like symptoms in mice via NF k B/p38MAPK signaling in the brain. IL-17A administration per se also causes elevation of inflammatory mediators in brains areas associated with depression. NF k B/p38MAPK inhibitor attenuates IL-17A-induced depression-like symptoms. Abstract: Psoriasis has been shown to be associated with an increased prevalence of comorbid major depression. IL-17A plays an important role in both depression and psoriasis. IL-17A has been shown to be elevated in systemic circulation of psoriatic patients. IL-17A released from different immune cells during psoriasis may be responsible for the development of neuropsychiatric symptoms associated with depression. Therefore, this study explored the association of systemic IL-17A with depression. The present study utilized imiquimod model of psoriatic inflammation as well as IL-17A administration in mice to investigate the effect of IL-17A on depression-like behavior. Psoriatic inflammation led to enhanced IL-17A expression in peripheral immune cells of both innate and adaptive origin. This was associated with increased NFκB/p38MAPK signaling and inflammatory mediators in different brain regions, and depression-like symptoms (as reflected by sucrose preference and tail suspension tests). The role of IL-17A was further confirmed by administering it alone for ten days, followed by assessment of the same parameters. IL-17A administration produced effects similar to psoriasis-like inflammation on neurobehavior and NFκB/p38MAPK pathways. Moreover, both NFκB and p38MAPK inhibitors led to attenuation in IL-17A associated with depression-like behavior via reduction in inflammatory mediators, such as MCP-1, iNOS, IL-6, and CXCL-2. Furthermore, anti-IL17A antibody also led to a reduction in imiquimod-induced depression-like symptoms, as well as NFκB/p38MAPK signaling. The present study shows that IL-17A plays an important role in comorbid depression associated with psoriatic inflammation, where both NFκB and p38MAPK pathways play significant roles via upregulation of inflammatory mediators in the brain.